After the Boom-Commodity Prices and Economic Growth in Latin America and the Caribbean - Gruss, Bertrand (Washington, D.C. : International Monetary Fund, 2014)
After skyrocketing over the past decade, commodity prices have remained stable or eased somewhat since mid-2011-and most projections suggest they are not likely to resume the upward trend observed in the last decade. This paper analyzes what this turn in the commodity price cycle may imply for output growth in Latin America and the Caribbean. The analysis suggests that growth in the years ahead for the average commodity exporter in the region could be significantly lower than during the commodity boom, even if commodity prices were to remain stable at their current still-high levels. Slower-than-expected growth in China represents a key downside risk. The results caution against trying to offset the current economic slowdown with demand-side stimulus and underscore the need for ambitious structural reforms to secure strong growth over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet